Stylistic Analysis of Body Positivity Movement Campaign on Pinterest - Zainal Arifin Renaldo (ELT-Lectura, 2022)
The emergence of body positivity movement has been popular in online media as the result of society’s awareness towards the phenomenon of body image shaping by media, culture, as well as society itself. The concept of ideal body image has forced people especially women to meet the standard that is often demanding and endangering. Moreover, the rise of social media worsens this phenomenon as social media users are now more exposed to those images. Many parties that have concern in this issue show their concern in bringing awareness to people by posting banners containing body positivity campaign in online media platform, one of which is Pinterest. This research is aimed at investigating the use of figurative language in body positivity movement campaign from the perspective of stylistic analysis. The lexical and syntactic structures of the utterance are also identified. The result shows that from 33 data collected, the type of figurative language used are personification, metaphor, paradox, hyperbole, simile, and synecdoche in which personification is found to be the most frequent figurative language in the banners. The use of phrase and simple sentence are also the most dominant lexical and syntactic structures used by the creator.